Biocompatibility assessment of bioceramic repair cements: An in vivo study in wistar rats (Research, Society and Development, 2021)
The aim of this study was to evaluate the biocompatibility of Biodentine® bioceramic repair cement when compared to White Angelus MTA® and calcium hydroxide. Twenty-four Wistar rats were used (n = 6 animals / group), divided into four experimental periods of 7, 15, 30 and 60 days. The animals received subcutaneous implants of polyethylene tubes containing the 3 test materials and an empty tube used as control. After experimental periods, animals were euthanized and the tubes were removed along with the adjacent surrounding tissue and histologically processed to assess biocompatibility. Inflammatory infiltrate and fibrous capsule thickness were analyzed by HE staining through inflammation scores. Data was submitted to Kruskal Wallis and Dunn’s test (p